The spacecraft and Science Communicator roles in human missions: Lessons learned from testing various architectures in the Desert RATS field tests. (April 2019) - Yingst, R. Aileen; Lederer, Susan M.; Love, Stanley G.
Abstract: The Desert RATS field analogue tests in 2010 and 2011 utilized the position of Science Communicator (SciCom) as that of a communications facilitator among the test's astronaut crews, science backrooms, and flight operations team. Based on the traditional role of the Spacecraft Communicator (CapCom), the SciCom was tasked with utilizing their science expertise to understand the inputs from the science backroom, and to quickly and effectively distill those into executable tasks communicated to the crew. The role was demonstrated to be a crucial component of the success of these tests. Certain skills were determined to be essential for a SciCom to develop; these included science knowledge germane to the mission, good communications skills, diplomacy, the ability to multitask, and the ability to advocate for the crew. Key attributes of the SciCom role include: the ability to balance science team goals and requirements with crew needs on a science-driven tactical timeline; using good judgment, strong situational awareness, foresight, and experience to meet the needs of each team; fostering a good relationship with their Science Lead (SciLead); anticipating and being proactive in addressing issues; and strengthening constructive cross-referencing and cross-education with the SciLead. These attributes mimic the relationship between the CapCom and the Flight Director. Highlights: The Science Communicator facilitates communication in field analogue tests. SciComm turns science backroom desires into executable tasks for the crew. SciComm must be a good scientist, communicator, diplomat and multitasker. SciComm must balance science and crew needs tactically. SciComm must use good judgment and foresight to meet team needs.